Disturbance observer-based control for nonlinear systems subject to mismatched disturbances with application to hypersonic flight vehicles. (22nd March 2017) - Li, Yunling; Zeng, Ming; An, Hao; Wang, Changhong
For a class of multi-input multi-output nonlinear systems, a disturbance observer-based control is proposed to solve the tracking problem in the presence of mismatched disturbances. By designing a novel compensation gain matrix, the disturbances can be removed from the output channel completely as well as retaining the nominal performance. Compared with the state of the art, the gain matrix reduces to be constant; therefore, the complexity of the controller is simplified greatly. This method is applied to the control of hypersonic flight vehicles to demonstrate its effectiveness.